Commodities and Development Report 2021 - United Nations Conference on Trade; Development (United Nations, 2021)
Commodity dependence is a trap: once a country is commodity dependent, it is difficult to develop a productive sector out of commodities and export non-commodity products. This publication argues that without strong action at the highest political level in Commodity-dependent Developing Countries (CDDCs), these countries will remain trapped for centuries. It demonstrates how technology and innovation could lead the way to economic and structural transformation in CDDCs, helping to diversify economies and lessen dependence on the commodity sector and, in turn, strengthen productivity growth. Enabling CDDCs to escape from the commodity dependence trap requires stronger cooperation between CDDCs and their trading and development partners with regard to technological acquisition and domestication. Indeed, a conducive framework for technology accessibility and its transfer to CDDCs is ultimately needed at the international level.